Standards without standardisation? Assembling standards-based reforms in Australian and US schooling. Issue 6 (1st November 2020) - Lewis, Steven; Savage, Glenn C.; Holloway, Jessica
ABSTRACT: Our aim in this paper is to examine how standards-based reforms (SBRs) relating to teachers and teaching are being constituted in Australia and the US. Our focus is not the specific impacts of these policies as enacted practices in schools or teacher training institutions, but rather the dynamics of policy production, with a specific focus on how federally-driven policies have been assembled in each country. Bringing together the notion of 'global forms' with the dual concepts of 'political rationality' and 'political technology' from governmentality studies, we consider SBRs as a global techno-scientific form that coheres at the level of political rationality and which can be abstracted across contexts, but which also manifests in unique place-specific assemblages of political technologies. The global form of SBRs thus represents the logics by which policymakers may attempt to align and create commonality across systems in the search for standardisation, even if this can never be fully realised in practice.